Interrupting the trajectory of frailty in dementia with Lewy bodies with anabolic exercise, dietary intervention and deprescribing of hazardous medications. Issue 4 (26th April 2020) - Inskip, Michael; Mavros, Yorgi; Sachdev, Perminder Singh; Fiatarone Singh, Maria A
Abstract : An 87-year-old man with dementia with Lewy bodies, living in residential aged care, exhibited rapid functional decline and weight loss associated with injurious falls over 9 months. Independent clinicians (geriatrician and exercise physiologist) assessed him during an extended wait-list period prior to his commencement of a pilot exercise trial. The highly significant role of treatable factors including polypharmacy, sarcopenia and malnutrition as contributors to frailty and rapid functional decline in this patient are described. The results of a targeted intervention of deprescribing, robust exercise and increased caloric intake on his physical and neuropsychological health status are presented. This case highlights the need to aggressively identify and robustly treat reversible contributors to frailty, irrespective of advanced age, progressive 'untreatable' neurodegenerative disease and rapidly deteriorating health in such individuals. Frailty is not a contraindication to robust exercise; it is, in fact, one of the most important reasons to prescribe it.